12 days of altitude exposure at 1800 m does not increase resting metabolic rate in elite rowers - Woods, A. L.; Garvican-Lewis, L. A.; Rice, A.; Thompson, K. G. (Applied Physiology, Nutrition, and Metabolism, 2017)
Four elite rowers completed a 12-day altitude training camp living at 1800 m, and training at 1800 m and 915 m, to assess changes in resting metabolic rate (RMR). RMR and body composition were assessed pre- and postcamp. Downward trends in RMR and body composition were observed postaltitude: absolute RMR (percent change: -5.2%), relative RMR (-4.6%), body mass (-1.2%), and fat mass (-4.1%). These variations are likely related to the hypoxic stimulus and an imbalance between training load and energy intake.